Intraventricular topotecan in the successful treatment of recurrent CNS pleuropulmonary blastoma. Issue 3 (16th December 2021) - Shim, Jenny; Reisner, Andrew; Esiashvili, Natia; Rapkin, Louis; Olson, Thomas
Abstract: Pleuropulmonary blastoma (PPB) is a rare pediatric tumor of the pleura and pulmonary mesenchyme, associated with pathogenic germline DICER1 mutations. Although the most common site of metastasis is the central nervous system (CNS), patients with CNS metastasis have dismal outcome. We report a case of a patient presenting with type II PPB and intracranial and bone metastases. We describe a multimodal therapy approach and highlight the use of intraventricular topotecan for isolated CNS recurrence. In addition, a new pathogenic germline mutation heterozygous for the c.1234delT of DICER1 was identified. Patient remains in remission 3 years after recurrence.